VD_FINDINFO AM 27/21 - 9/2022 vom 28. Februar 2022 - VD Tribunal cantonal (2022)
TRAITEMENT DENTAIRE, ASSURANCE OBLIGATOIRE, REJET DE LA DEMANDE | 25 LAMal, 31 al. 1 LAMal, 33 al. 2 LAMal, 17 OPAS, 18 OPAS, 19 OPAS